2021
DOI: 10.3390/ma14102632
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Timber−Lightweight Concrete Composite Beams with Ductile Bolt Connectors

Abstract: A timber–lightweight−concrete (TLC) composite beam connected with a ductile connector in which the ductile connector is made of a stainless−steel bolt anchored with nuts at both ends was proposed. The push−out results and bending performance of the TLC composite specimens were investigated by experimental testing. The push−out results of the shear specimens show that shear–slip curves exhibit good ductility and that their failure can be attributed to bolt buckling accompanied by lightweight concrete cracking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Several researchers have been investigating the feasibility of different connections among TCCs. Following these, a considerable body of work has been carried out to build high-performance shear connectors and quantify the load slip, load-bearing capacity, and stiffness of the connections, mostly via push-out-shear tests [21][22][23][24][25][26]. e connection in TCC was found to affect the load-bearing behavior of the composite beam, while the structural behavior of the slab was influenced by the stiffness, ductility, and shear resistance of the connection [27,28].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have been investigating the feasibility of different connections among TCCs. Following these, a considerable body of work has been carried out to build high-performance shear connectors and quantify the load slip, load-bearing capacity, and stiffness of the connections, mostly via push-out-shear tests [21][22][23][24][25][26]. e connection in TCC was found to affect the load-bearing behavior of the composite beam, while the structural behavior of the slab was influenced by the stiffness, ductility, and shear resistance of the connection [27,28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…e motivation of the study is to investigate timber-concrete composite structural design, which consists of a concrete slab, where concrete is designed to be in the compression zone, and the timber is attached below in the tension zone. ese two materials are combined using different shear connectors, such as coach screw shear connectors (zinc-plated steel coach screw), stud connectors, dowels, and notches cut in the timber filled with concrete [20][21][22][23][24][25][26][27][28][29][30]. e shear connection between timber and concrete is essential as these connectors typically govern the strength and the structural behavior of the TCC structures.…”
Section: Motivation Of Researchmentioning
confidence: 99%
“…It was demonstrated that the deconstructable connection possesses the similar shear behaviors compared with the permanent connections. In addition, Crocetti et al [18], Zhang et al [19], and Hu et al [20] also provided the feasible assembly-type connecting methods for TCC structures based on the dowel-type connections. Tao et al [21] investigated shear performances of the cross inclined screw connections using prefabricated slabs through the grouting method, and obtained the expected experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] In recent years, studies have indicated that bamboo engineering materials are suitable not only for decoration and furniture but also for building structures [7][8][9][10][11] and have been generally utilized in pedestrian bridges, residential buildings, and landscape buildings. [12][13][14][15] In bamboo engineering materials, reconstituted bamboo has excellent mechanical properties, [16][17][18] which is a research hotspot for new biomass engineering materials.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies of reconstituted bamboo mostly involve bending and compression members, 19 including ordinary restructuring bamboo beams and bamboo poles, 20,21 and the restructuring of bamboo, fiber reinforced polymer (FRP) and concrete, and wood composite structures. 18,[22][23][24][25] However, research on the impact of environmental temperature on the physical and mechanical properties of bamboo is limited. Presently, the effect of temperature on the mechanical performance of reconstituted bamboo research is mainly reflected in heat treatment.…”
Section: Introductionmentioning
confidence: 99%